Method for Studying the Multisoliton Solutions of the Korteweg-de Vries Type Equations. (17th June 2015) - Turbal, Yuriy; Bomba, Andriy; Turbal, Mariana
Abstract : We present a new approach to find travelling wave solutions for the Korteweg-de Vries type equations, which allows extending the class of known soliton solutions. Also we propose method for studying the multisoliton solutions of the Korteweg-de Vries type equations.